Superior Temporal Gyrus (STG) and cerebellum show different activation profile during simple arithmetic addition task in quiet and in noisy environment: an fMRI study - Ahmad Nazlim Yusoff; Teng, Xin Ling; Aini Ismafairus Abd Hamid; Siti Zamratol-Mai Sarah Mukari (Penerbit Universiti Kebangsaan Malaysia, 2016)
Despite a vast number of studies that were focused on the roles of superior temporal gyrus (STG) and cerebellum as sensory area, little is known about their involvement in cognitive function such as attention and perception. The present fMRI study aimed to identify this cognitive role from brain activation profile of STG and cerebellum obtained from an arithmetic addition task. Eighteen healthy right hand dominance male adults participated in this study. They were instructed to solve single-digit addition tasks in quiet and noisy background during the fMRI scan. Both the in-quiet and in-noise addition tasks activated the bilateral STG and cerebellum (lobule VI and lobule VII) significantly but differentially. In both quiet and noisy conditions, STG activation is dominant in the left hemisphere while cerebellum showed a right hemisphere dominance. Bilateral STG and cerebellum (lobule VI) activation decreasedin noise, conversely cerebellum (lobule VII) activation increased in noise. These asymmetrical activation indicated hemispheric lateralization and differential behaviors of both brain areas in different environment while performing simple arithmetic addition task.